Prevalence of hormonal contraceptive use and self-reported symptomatic experiences attributed to the menstrual cycle or hormonal contraceptive use in Norwegian women: the effect of training categories and age groups - the FENDURA project - Osborne, J. O.; Storvand, J. H.; Engseth, T. P.; Solli, G. S.; Morseth, B.; Taylor, M. Y.; Welde, B.; Elliott-Sale, K. J.; Andersson, E. P.; Sandbakk, Ø.; Noordhof, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The aims of the current study were to (1) report the prevalence of hormonal contraceptive (HC) use among Norwegian women across different training categories and age groups; (2) compare the frequency and severity of cycle-related symptoms across differing training categories and age groups; and (3) describe the bleeding pattern and prevalence of menstrual disorder/disturbances among non-HC users. A sample of 2059 Norwegian women completed a survey reporting: weekly training volume; current HC usage, type, and reasons for use; cycle-related symptom frequency and severity; and the prevalence of menstrual disorders/disturbances. Respondents were categorized by age (youth: 13-20; young adults: 21-30; older adults: 31-50 years) and training category (minimal: 0; low: < 5; moderate: 5-9; high: = 9 h·week-1). Half (51.6%) of respondents reported current HC usage, predominantly long-acting reversible contraception or combined oral contraceptives. Young adults had the highest prevalence of HC use (62.7%) compared to youth (48.4%) and older adults (43.8%), although no differences in usage were seen across training categories. HC users reported fewer and less severe cycle-related symptoms compared to non-users. A third (30.8%) of non-HC users had experienced a menstrual disorder/disturbance, with no significant differences observed across training categories or age groups. In conclusion, HC use is widespread among Norwegian women, with no differences between training categories. This similar HC prevalence suggests that HC research conducted in female cohorts may be generalizable, independent of training category. However, attention should be paid to participants' age due to differences in HC use between age groups.